Β-Lactoglobulin hydrolysis by a flow-through monolithic immobilized trypsin reactor in ethanol/aqueous solvents. (July 2019) - Mao, Yuhong; Krischke, Maria; Kulozik, Ulrich
Graphical abstract: Highlights: Reducing agents showed varied effects on immobilization yield and activity. Activity of immobilized trypsin increased by 20% in 20% ethanol/water. 20% ethanol increased the hydrolysis of β-Lg by immobilized trypsin. Releases of peptides locating inner β-Lg increased in 20% ethanol than in water. Abstract: Monolith based immobilized trypsin reactors (MITRs) were developed using different immobilization protocols. Compared with the use of reducing agent NaCNBH3, the application of 2-PB led to around 33% decrease in immobilization yield, while improved the specific activity of immobilized trypsin. The developed flow-through MITR was used to hydrolyze β-Lactoglobulin (β-Lg), and the feasibility of integrating ethanol in reaction media was evaluated. Raising ethanol concentrations from 0 to 50% increased the size of β-Lg molecules from 1.74 ± 0.32 nm to 5.67 ± 2.78 nm, and doubled the viscosity of β-Lg solutions. To avoid high backpressure and potential clog on MITR, β-Lg was hydrolyzed with the addition of ethanol up to 20%, where the activity of immobilized trypsin increased by 20% than that in aqueous media. Similar to free trypsin, the addition of ethanol contributed to an increase in DH and a faster depletion of intact protein for MITR. The presence of ethanol decreased the releases of peptides locating on C- termini, i.e., f(149–162) and f(142–148) for free and immobilized trypsin. However, the release of peptides locating inner β-Lg increased, e.g., a 5 times higher amount of f(125–138) was detected for MITR in 20% ethanol.